Daily brisk walking increases intestinal acetic acid in short-chain fatty adults in healthy young adults: A randomized controlled trial - Emiko Morita; Suguru Ando; Yumi Fukuyama; Yui Kikuchi; Sho Kumabe; Yoshihiro Yamashina (BioSocial Health Journal)
Introduction: In this study, we aimed to investigate the effect of daily physical activity levels, specifically brisk walking, on short-chain fatty acid (SCFA) production through the modulation of SCFA-producing bacteria in young individuals. Methods: This 12-week randomized comparative trial included 30 participants. The participants were assigned to either the group that walked 8000 steps daily, including 20 minutes of brisk walking at an intensity of≥5 metabolic equivalents (BW group), or the group that walked 8000 steps daily at their customary pace (CP group). The SCFA levels and composition of the intestinal microbiota were assessed before and after the intervention. Daily physical activity and cardiorespiratory fitness were monitored using an accelerometer and the incremental shuttle walking test (ISWT), respectively. Results: The BW group exhibited a significant increase in the level of acetic acid, a type of SCFA, following the intervention. The relative abundance of intestinal Bifidobacterium was significantly higher in participants who successfully completed 20 minutes of brisk walking during the intervention. Conclusion: Daily brisk walking for 20 minutes enhances acetic acid production by fostering the proliferation of Bifidobacterium in young individuals.